2013
DOI: 10.1111/adj.12091
|View full text |Cite
|
Sign up to set email alerts
|

Effect of non‐surgical periodontal treatment on HbA1c: a meta‐analysis of randomized controlled trials

Abstract: Background: A meta-analysis of randomized clinical trials (RCTs) was conducted to evaluate whether non-surgical periodontal treatment can reduce the HbA1c% level in type 2 diabetic patients. Recent accumulation of RCTs necessitates updating of the findings of previous reviews. Methods: A search of the literature on English publications was conducted in Cochrane CENTRAL, Medline and EM-BASE (until 31 March 2012). An RCT was selected if the study population was type 2 diabetic patients (≥16 years old) diagnosed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
29
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 40 publications
7
29
0
4
Order By: Relevance
“…Several meta‐analyses concluded that there is evidence that periodontal treatment has a modest effect on glycaemic control in individuals with diabetes (Darre, Vergnes, Gourdy, & Sixou, ; Engebretson & Kocher, ; Liew, Punnanithinont, Lee, & Yang, ; Sgolastra, Severino, Pietropaoli, Gatto, & Monaco, ; Simpson, Needleman, Wild, Moles, & Mills, ; Teeuw, Gerdes, & Loos, ) (Table , Figure ). The review by Taylor et al.…”
Section: Resultsmentioning
confidence: 99%
“…Several meta‐analyses concluded that there is evidence that periodontal treatment has a modest effect on glycaemic control in individuals with diabetes (Darre, Vergnes, Gourdy, & Sixou, ; Engebretson & Kocher, ; Liew, Punnanithinont, Lee, & Yang, ; Sgolastra, Severino, Pietropaoli, Gatto, & Monaco, ; Simpson, Needleman, Wild, Moles, & Mills, ; Teeuw, Gerdes, & Loos, ) (Table , Figure ). The review by Taylor et al.…”
Section: Resultsmentioning
confidence: 99%
“…Eight SRs included randomized controlled trials (RCTs) only, and three SRs RCTs and controlled clinical trials. Most RCTs included in the SRs presented at least one of the domains assessed with unclear or high risk of bias.…”
Section: Resultsmentioning
confidence: 99%
“…When not reported, it was calculated for the intervention and the control groups by means of the formula [35]:where HbA1c f is the mean HbA1c value after treatment and HbA1c b is the mean HbA1c value before treatment. And if the standard deviation was not reported, it was obtained by the formula [35], [38]:Where SD c is the standard deviation of mean change of HbA1c, SD b is the standard deviation of mean baseline HbA1c values, SD f is the standard deviation of mean end HbA1c values. Corr is the correlation between the baseline and end values, it was set at 0.5, consistent with the previous reviews [35], [38].…”
Section: Methodsmentioning
confidence: 99%
“…And if the standard deviation was not reported, it was obtained by the formula [35], [38]:Where SD c is the standard deviation of mean change of HbA1c, SD b is the standard deviation of mean baseline HbA1c values, SD f is the standard deviation of mean end HbA1c values. Corr is the correlation between the baseline and end values, it was set at 0.5, consistent with the previous reviews [35], [38].…”
Section: Methodsmentioning
confidence: 99%